A visuospatial “phonological loop” in working memory: Evidence from American Sign Language - Wilson, Margaret; Emmorey, Karen (Memory & cognition, 1997)
In two experiments, the question of whether working memory could support an articulatory rehearsal loop in the visuospatial domain was investigated. Deaf subjects fluent in American Sign Language (ASL) were tested on immediate serial recall. In Experiment 1, with ASL stimuli, evidence was found for manual motoric coding (worse recall under articulatory suppression) and previous findings of ASL-based phonological coding (worse recall for phonologically similar lists) were replicated [corrected]. The two effects did not interact, suggesting separate components which both contribute to performance. Stimuli in Experiment 2 were namable pictures, which had to be recoded for ASL-based rehearsal to occur. Under these conditions, articulatory suppression eliminated the phonological similarity effect. Thus, an articulatory process seems to be used in translating pictures into a phonological code for memory maintenance. These results indicate a configuration of components similar to the phonological loop for speech, suggesting that working memory can develop a language-based rehearsal loop in the visuospatial modality.